A Lateglacial and early Holocene pollen record from Valle di Castiglione (Rome): Vegetation dynamics and climate implications - Di Rita, Federico; Anzidei, Anna Paola; Magri, Donatella (Quaternary International, 2013)
A new pollen record from Valle di Castiglione near Rome (core VdC09) has been studied with the aim of providing a detailed reconstruction of the vegetation history of the Roman landscape between 13,800 and 7700 cal BP, in response to the Lateglacial and early Holocene climate events. An open landscape dominated by steppe vegetation characterized the Lateglacial, so that only a modest increase of trees took place during the Allerød interstadial. The Intra Allerød Cold Period induced instability in the development of the woody communities. The Holocene forest recovery started around 11,600 cal BP, but definite forest development occurred only around 11,100 cal BP, at the end of the Preboreal Oscillation, which produced an important re-expansion of herbs. The evergreen Mediterranean vegetation was constantly present in the landscape, even during the Lateglacial cold fluctuations. A clear early Holocene increase in evergreen trees corresponds to the attainment of high and stable values in the GISP2 δ18O curve, around 10,200 cal BP.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd and INQUA
Keywords: climate changes; deciduous and evergreen forests; Holocene; landscape (voyant); Mediterranean Region; Pollen analysis; Vegetation dynamics